Kobieta i kobiecość w twórczości Brunona Schulza i Borisa Viana – analiza porównawcza - Nachyła, Piotr (Językowe, literackie i kulturowe refleksje na temat jedności w różnorodności, 2023)
A comparison of the representation of female characters in the works of Boris Vian and Bruno Schulz. The following article posits that female characters are subject to a certain stereotyping that is characteristic of both authors. The reasons for this representation of female characters may have their roots in the biographies of the authors. Both seem to draw on the same cultural patterns. The author of this article tries to draw a picture of the era in which both artists worked with a particular focus on the role of women, which also applies to the literary text. Using numerous examples from the works of both Bruno Schulz and Boris Vian, he attempts to describe the characteristic elements of aesthetics common to both authors.